Kinerja Rantai Pasok Beras di Kabupaten Karawang : Performance of Rice Supply Chains in Karawang District - Nurmahdy , Ahmad Irfan; Machfud, Machfud; Syuaib, M. Faiz Syuaib (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
Karawang Regency is an area of rice production center which will be a model for supply chain studies in this research. This study aims to determine the condition of the rice supply chain, determine the performance of the rice supply chain, and formulate efforts to improve the performance of the rice supply chain. The method used is the Food Supply Chain Network (FSCN) and Supply Chain Operation Network (SCOR) approaches. Based on the results of research members of the rice supply chain starts from farmers, traders, and rice mills. The value of performance metrics for farmers that are still not in line with expectations include the metric for orders delivered in full, perfect conditions, production costs, ranges of debt and receivables payments. Obtained several factors causing ineffective and inefficient performance of the rice supply chain in Karawang regency in each supply chain actor. Factors affecting farmers are the high cost of farming and the long range of payment of receivables can be overcome by increasing knowledge and application of technological developments and agricultural machinery, and strengthening the function of farmer groups. Factors affecting collecting traders are the low value of suitability of procurement flexibility. Factors affecting the low performance of rice milling are procurement flexibility and shipping flexibility.Keywords: effort to improve the performance, paddy, performance measurement, SCOR, supply chain